The Relationship Between Level of Physical Fitness With Learning Outcomes at Class XI Students of SMA 4 Seram Timur District - Iksan Rumodar; Bahmid Hasbullah; Welhelima Unmehopa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the level of physical fitness with the learning outcomes of class XI students of SMA 4, East Seram Regency. Physical fitness is a condition in which the body shows a healthy condition physically and mentally when carrying out daily activities or working involving very heavy physical abilities without having to experience significant fatigue and is able to recover energy before the next task comes, also still has residual energy. energy to fill spare time. (Moh and Tomasoa 2020). In this study, a correlation technique was used, namely to involve the relationship between the level of physical fitness and PJOK learning outcomes in class XI SMA 4 East Seram Regency with a correlational research design with a descriptive quantitative approach.